Construction of BAC and BIBAC libraries and their applications for generation of SSR markers for genome analysis of chickpea, Cicer arietinum L. - Lichtenzveig, Judith; Scheuring, C.; Dodge, J.; Abbo, S.; Zhang, H. (Springer, 2005)
Large0insect bacterial artificial chromosome (BAC) libraries, plant-transformation-competent binary BAC (BIBAC) libraries, and simple sequence repeat (SSR) markers are essential for many aspects of genomics research. We constructed a BAC library and a BIBAC library from the nuclear DNA of chickpea, Cicer arietinum L., cv. Hadas, partially digested with Hindlll and BamHI, respectively. The BAC library has 14,976 clones, with an average insert size of 121 kb and the BIBAC library consists of 23,040 clones, with an average insert size of 145 kb. The combined libraries collectively cover ca. 7.0• genomes of chickpea. We screened the BAC ibrary with eight synthetic SSR oligos, (GA)10, (GAA)7, (AT)10, (TAA)7, (TGA)&, (CA)10, (CAA)7, and (CCA)7. Positive BACs were selcted, subcloned, and sequenced for SSR marker development. Two hundred and thirty-three new chickpea SSR markers were developed nad characterized by PCR, using chickpea DNA as template. These results have demonstrated that BACs are an excellent source for SSR marker development in chickpea. We also estimated the distribution of the SSR loci in the chickpea genome. The SSR motifs (TAA)n and (GA)n were much more abundant than the others, and the distribution of the SSR loci appeared non-random. The BAC and BIBAC libraries and new SSR markers will provide valuable resources for chickpea genomics research and breeding (the libraries and their filters are available to the public at http://hbz.tamu.edu).